Analyzing media messages using quantitative content analysis in research - Riffe, Daniel; Lacy, Stephen 1948-; Watson, Brendan R.; Fico, Frederick
"The fifth edition of this comprehensive and engaging text guides readers through the essential tools and skills necessary to conduct quantitative content analysis research. Readers will find a clear definition of quantitative content analysis and step-by-step instructions on designing a content analysis study, along with examples of content analysis studies and journal articles. This edition has been updated with the latest methods in sampling in the digital age, computerized content analysis, and the uses of social media in content analysis research. It maintains the concise, accessible approach of previous editions while including refreshed examples and discussions throughout. This is an essential text for content analysis courses in communication and media studies programs of all levels, as well as a useful supplementary text in more general research methods courses"--Provided by publisher.
Introduction -- Defining content analysis as a social science tool -- Designing a content analysis -- Computers and content analysis -- Measurement -- Sampling -- Reliability -- Validity -- Data analysis.
First edition published by Routledge 1998. Fourth edition published by Routledge 2019.
NMGlova ( Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Content analysis (Communication); Mass media -- Research -- Methodology; Mass media -- Statistical methods